Dukungan Keluarga, Karakteristik dan Efektivitas Kompres Hangat Kayu Manis terhadap Penurunan Skala Nyeri Rheumatoid Arthritis - Sembiring, Muhammad Nur Maghribi; Nasution, Siti Zahara; Nurhidayah, Rika Endah (Journal of Telenursing (JOTING), 2024)
This study aims to identify and analyze the influence of family support before and after the action, the characteristics of family members, the influence of the action, and the effectiveness of the action of warm cinnamon and warm compresses on reducing the pain scale for rheumatoid arthritis. This research method is quantitative with a quasi-experimental research design using a pre-test and post-test design with a warm compress control group. The sampling method in this study used total sampling, so the number of samples for each group was: 30 people for the control group and 30 people for the intervention group. This research began in September 2023 – February 2024. Based on the results of statistical tests using the Mann-Whitney and Wilcoxon tests, the P-value was obtained, namely 0.000 < α = 0.05. In conclusion, there is the influence of family support before and after the action is taken, there is the influence of warm cinnamon compresses and warm compresses, then there is the effectiveness of warm cinnamon compresses and warm compresses on reducing the scale of rheumatoid arthritis pain. Keywords: Warm Cinnamon Compress, Pain, Rheumatoid Arthritis.